Bias Gender dalam Perkawinan Nyentana pada Masyarakat Desa Cemagi, Kabupaten Badung - Kusumayanti, Ni Kadek Shinta; Maheswari, Anak Agung Istri Agung (VISA: Journal of Vision and Ideas, 2025)
This study analyzes gender bias in nyentana marriage practices among the people of Cemagi Village, Badung Regency, using Pierre Bourdieu's Theory of Social Practice Capital. Through a qualitative descriptive approach using interviews, observation, and documentation techniques, this study reveals how men who enter women's families experience shifts in habitus, social roles, and symbolic authority. The results show that even though nyentana is formally recognized in customary law and men obtain equal ritual rights after being approved as krama, social acceptance does not occur automatically. Men must rebuild their social and symbolic capital through active participation in banjar activities and other customary obligations. Gender bias is evident in three main aspects: (1) community perceptions that position nyentana men as subordinate; (2) symbolic violence through everyday language such as “follow your wife” or “megolih”; and (3) the distribution of economic, social, and symbolic capital that is not yet fully equal in women's families. For female families, nyentana is a strategy for preserving the family line and increasing the family's symbolic capital. This study recommends the formulation of more gender-sensitive customary regulations, the use of more inclusive language, and community education to reduce bias and symbolic violence in the practice of nyentana in Bali.